2022
DOI: 10.3390/ph15040464
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects and Human Health Benefits of Hibiscus sabdariffa: A Review of Clinical Trials

Abstract: Hibiscus sabdariffa Linn. Malvaceae (HS) is characterized by its edible calyxes. The HS calyxes are widely used for cosmetic, food, and medicinal applications. According to ethnobotanical evidence, decoction, infusion, or maceration extracts from HS calyxes have been used in folk medicine to treat many ailments. Moreover, several in vitro and in vivo studies have demonstrated the pharmacological properties and potential human health benefits of HS consumption. On the other hand, the evaluation of the physiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 108 publications
0
13
0
Order By: Relevance
“…The T. speciosum extract presented a slight higher TPC value (640 mg EAG/g) [18], and H. rosa-sinensis L. showed a lower value of antioxidant activity (DPPH 145 ± 3 mg TE/100 g DW) [21] than the extract of H. acetosella flowers. Several studies both in vitro and in vivo have shown that extracts of Hibiscus present a potent antioxidant effect due to its strong scavenging effect on reactive oxygen and free radicals [19,22]. The results found herein contribute to stimulating the consumption of edible flowers as a functional food as well as stimulating their use as sources of natural antioxidants by the food industry [23].…”
Section: Physicochemical Characterization Centesimal Composition and ...mentioning
confidence: 61%
“…The T. speciosum extract presented a slight higher TPC value (640 mg EAG/g) [18], and H. rosa-sinensis L. showed a lower value of antioxidant activity (DPPH 145 ± 3 mg TE/100 g DW) [21] than the extract of H. acetosella flowers. Several studies both in vitro and in vivo have shown that extracts of Hibiscus present a potent antioxidant effect due to its strong scavenging effect on reactive oxygen and free radicals [19,22]. The results found herein contribute to stimulating the consumption of edible flowers as a functional food as well as stimulating their use as sources of natural antioxidants by the food industry [23].…”
Section: Physicochemical Characterization Centesimal Composition and ...mentioning
confidence: 61%
“…and Malic acid It is rich in beta-carotene, glucose, and vitamin C. Phenolic compounds work and facilitate digestion. It also has a great importance that works to continuously form beneficial bacteria in the intestine and inhibit the proliferation of harmful bacteria [5] and [10]. Cucumbers contain glycosides, where glycosides activate enzymes to produce metabolic reactions that interfere with proteins [11] and thus kill harmful microorganisms that cause protein oxidative damage [12].…”
Section: Relative Weight Of Edible Internal Organsmentioning
confidence: 99%
“…The use of broiler meat has flourished at the present time, both internationally and locally, due to the abundance of benefit from it [1] because it contains poultry meat, the high ability to transform the nutritional mass into elements to benefit the body from it and fill the deficiency in the body as a result of the composition of the basic elements [2] Lately, I preferred to use medicinal plants for its many benefits, and it is given to poultry because it is a natural additive instead of adding chemical compounds that are deposited in the body and has many harms to humans, and also because it contains many effective substances, including flavonoids, polyphenols, saponins, glycosides, and others [3] Hibiscus Sabdariffa plants are included in medicinal and food plants that possess a therapeutic property [4], and its leaves are characterized by being rich in active active substances, including 1262 (2023) 072083 IOP Publishing doi:10.1088/1755-1315/1262/7/072083 2 hepsin hydrochloride [5] Red tea has two acids, tartaric acid and citric acid, which improve the absorption of nutrients [6].…”
Section: Introductionmentioning
confidence: 99%
“…The main flavonoids in Rosella are Gossypetin, Hibiscetine, Luteolin, and Quercetin 7-9 . Rosella's flavonoid compounds and phenolic acids provide health benefits, including antiinflammatory, antioxidant, antihypertensive, hypolipidemic, antidiabetic, antimicrobial, and anticarcinogenic [10][11][12] .…”
Section: Introductionmentioning
confidence: 99%